TEM studies of multilayer ohmic contacts to n-type AlGaN/GaN - Fay, Mike W.; Moldovan, Grigore; Harrison, Ian; Balmer, R.S.; Soley, D.E.J.; Hilton, K.P.; Hughes, B.T.; Uren, M.J.; Martin, T.; Brown, Paul D. (IOP Publishing Ltd, 2003)
Ti and Pd barrier layers between the Al/Ti diffusion couple and the Au capping layer of multilayer ohmic contacts to n-type AlGaN/GaN field effect transistors were found to be ineffective in preventing the diffusion of Au to the AlGaN following high temperature rapid thermal annealing. The formation of a band of TiN grains at the contact/AlGaN interface is responsible for the activation of the contact. The presence of interfacial Au and threading dislocations are implicated in the formation of additional Ti-nitride inclusions into the AlGaN, although these do not appear to disrupt the Ti-nitride layer at the original contact/nitride interface, nor significantly influence the contact resistance.